2013
DOI: 10.5326/jaaha-ms-5833
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Anaphylaxis Induced by a Bumblebee Sting in a Dog

Abstract: A 3.5 yr old castrated male miniature schnauzer was referred with a history of collapse after a bee sting to the left hind limb. At the time of presentation, 14 hr after the sting, the dog was hypotensive, comatose, seizuring, and had a brief period of cardiac arrest. Over the following 48 hr, the dog developed azotemia, severely elevated liver enzyme levels, hypertension, hematochezia, hematemesis, and disseminated intravascular coagulation (DIC). The dog's neurologic status improved slowly, but significant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Bee venom is known to induce anaphylaxis‐related hemorrhage and coagulopathies in people, with reports of pulmonary, intracranial, and uterine bleeding . Disseminated intravascular coagulation and thrombocytopenia with secondary hemorrhage have also been reported with Hymenoptera envenomation in a dog . Given the documentation of a bee stinger in the dog in the current report, lack of known trauma and absence of a clear causative intra‐abdominal lesion on ultrasound, the hemoperitoneum in this case is suspected to be associated with alterations in hemostasis associated with anaphylaxis and bee envenomation.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Bee venom is known to induce anaphylaxis‐related hemorrhage and coagulopathies in people, with reports of pulmonary, intracranial, and uterine bleeding . Disseminated intravascular coagulation and thrombocytopenia with secondary hemorrhage have also been reported with Hymenoptera envenomation in a dog . Given the documentation of a bee stinger in the dog in the current report, lack of known trauma and absence of a clear causative intra‐abdominal lesion on ultrasound, the hemoperitoneum in this case is suspected to be associated with alterations in hemostasis associated with anaphylaxis and bee envenomation.…”
Section: Discussionmentioning
confidence: 55%
“…Consumptive coagulopathy is a noted complication of both Hymenoptera envenomation and anaphylaxis in the dog . In a clinical practice setting, a combination of PT, aPTT, platelet count, plasma fibrinogen concentration, and plasma d‐dimer concentration are used to make a presumptive diagnosis of disseminated intravascular coagulation .…”
Section: Discussionmentioning
confidence: 99%
“…However, massive envenomation may also kill those individuals that are not allergic to bee venom. In one study, bumblebee sting associated with anaphylactic shock has been reported in a dog [ 18 ]. Anemia, pale and congested mucous membranes, tense abdomen, obtundation, generalized seizure and episodic cardiac arrest were prominent findings in the affected animal.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia, pale and congested mucous membranes, tense abdomen, obtundation, generalized seizure and episodic cardiac arrest were prominent findings in the affected animal. The dog was treated symptomatically along with supportive therapy and recovered completely after six weeks [ 18 ]. Similar findings were presented in our report so the possibility of fatal honeybee sting associated with anaphylactic shock cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…The dog was discharged after seven days with ongoing polyuria, polydipsia, and behavioral changes. The polydipsia and polyuria resolved within a few days, but the behavioral changes continued for six weeks” [38]. In another case, a dog presented for respiratory stress and shock after being stung by >100 bees; acute lung injury/acute respiratory syndrome was diagnosed and after eight days of treatment with oxygen, steroids, antibiotics, and bronchodilators, the dog recovered [39].…”
Section: Venom Pathogenesis and Poisoning In Australiamentioning
confidence: 99%